PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, PRICE EARNING RATIO DAN FIRM SIZE TERHADAP FIRM VALUE (STUDI PADA BEBERAPA BADAN USAHA MILIK NEGARA DI INDONESIA) - Amanda Puspita Dewi Manda; Ferikawita M Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determinate the effect of the current ratio, debt to equity ratio, return on equity, price earning ratio and firm size on firm value in Badan Usaha Milik Negara (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample selection used purposive sampling technique and selected as many as 9 samples of companies from 20 populations of Badan Usaha Milik Negara (BUMN) companies. The data collection technique used is secondary data with data analysis technique is panel data regression analysis using Eviews 10 software and the best model is the fixed effect model (FEM). Based on the research results, partially current ratio, return on equity and price earning ratio have a positive effect on firm value, while partially debt to equity ratio and firm size does not affect on firm value. In addition, simultaneously current ratio, debt to equity ratio, return on equity, price earning ratio and firm size have an effect on firm value.